Novel, versatile and eco-compatible preparation of new 6-(1H-indol-3-yl)-2-oxo-4-aryl-1, 2, 3, 4-tetrahydropyrimidine-5-carbonitriles in water. (1st October 2013) - Fatma, Shahin; Singh, Divya; Mishra, Priya; Singh, Pravin; Ankit, Preyas; Singh, J.
A three-component, one-pot, simple and direct, highly efficient cyclocondensation method has been developed for the synthesis of 11 6-(1H-indol-3-yl)-2-oxo-4-aryl-1, 2, 3, 4-tetrahydropyrimidine-5-carbonitriles by combining an araldehyde with 3-(cyanoacetyl)-indole and urea in the presence of the cationic surfactant, CTAB and a catalytic amount of thiamine hydrochloride in water. A short reaction time, simple reaction conditions, ease of product isolation, and use of a cheap and readily available reusable catalyst make this method very attractive from an environmental and economic perspective.